HUBUNGAN BEBAN KERJA DAN KONSUMSI AIR MINUM DENGAN DEHIDRASI PADA PEKERJA PABRIK TAHU - Afton Ilman Huda; Tjipto Suwandi (The Indonesian Journal of Occupational Safety and Health, 2018)
Dehidration can significantly impact the workers of Tahu UD Sumber Kencana Factory due to workplace climate of warm environments. In addition, high metabolism also occurs because of job duties. Workers who inadequate hydrated while working lead to dehydration. This study aims to reveal the relationship of hydration status between workload and water intake. By applying observational research with cross sectional approach, this study obtained 14 workers in tahu (tofu) and cincau production. Workload data was collected by using 10 pulse measurement method by Kilbon (1992), while water intake measurement was conducted with observation sheet of NIOSH (2011). The urine colors chart by Armstrong (1994) and Armstong (1998) was used to indicate the hydration status of workers. The results showed that workload measurement included in mild and moderate category, whereas water intake measurement was mostly indicated workers in low category. Assessing the worker’s hydration status signified varied findings that were included mild, moderate, and severe category. The statistic analysis of Spearman’s rank correlation showed that the workload had low relation to dehydration (r = 0.094) and had high relation between water intake and hydration (r = 0.882). According to results, it can be concluded that dehydration is more likely to occur to workers with low water intake while working.Keywords: dehydration, water intake, workload